Bridging cultures: Factors influencing the academic and social experiences of international students at a higher education institution in South Africa - Solademi, Ayorinde; Oni, Olusola; Phillip, Julie (Journal of International Students, 2026)
The internationalization of higher education is a global priority, with international students fostering intercultural awareness and competencies. This study examined English language fluency, acculturative stress, and social connectedness among international students at the University of the Western Cape. A mixed-methods design was employed, including a structured survey of 256 students, focus groups, and stakeholder interviews. Data were analyzed using SPSS version 26 with descriptive and inferential statistics. The participants were predominantly male (53.9%), were aged 30–38 years and were pursuing postgraduate degrees (78.9%). Most lived alone (73.8%) and were unmarried (53.5%). Students reported high English proficiency but experienced moderate challenges with home sickness, discrimination, insecurity, and cultural adjustment. English fluency was negatively correlated with acculturative stress (r = –0.221, p < .05), whereas social connectedness explained 33% of the variance in stress (r = –0.573, p < .05). Language proficiency and social engagement influence adaptation, emphasizing the need for inclusive practices that support academic and emotional well-being.